Characterization of Bromelain from Morinda citrifolia (Noni) - Golden, K. D.; Smith-Marshall, J. (Journal of Scientific Research, 2012)
Morinda citrifolia from the Rubiaceae family, collected in parish of St. Andrew, Jamaica, West Indies, was investigated for the presence of the Bromelain-like protein enzyme. In the process Bromelain from Morinda citrifolia was partially purified and characterized. Fresh plant material was extracted in buffer (sodium acetate-acetic acid (10mM), L-cysteine (1mM), and sodium chloride (0.1M), freeze dried and analyzed using column chromatography and assayed using spectrophotometry in a five step procedure. The major purification steps involved were ammonium sulphate precipitation, gel-filtration (Sephadex G200), ion exchange chromatography (CM sephadex C25) and (DEAE sephadex A25). The protein content was determined using the Bradford method. The enzyme displayed an optimum activity at pH 7.1 and a temperature optimum at 35 ºC. A purification fold of 70.9 and percentage recovery of 3.3 was obtained. Inhibition studies using several different inhibitors of the enzyme revealed that the enzyme was susceptible to copper sulphate (0.1mM), mercury chloride (0.1mM), cobalt sulphate (0.1mM), zinc sulphate (0.1mM) and phenylmercury acetate (0.1mM). Both casein and p-Nitrophenylbenzyloxycarbonyl-L-lysinate (CLN) were used as substrates for the enzyme, with the enzyme displaying greater activity when using casein as substrate. Bromelain-like protein enzyme showed high affinity for the substrate casein with a Km of 48.5 µM. Key words: Morinda citrifolia; Bbromelain; Proteolytic enzyme. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i2.8125 J. Sci. Res. 4 (2), 445-456 (2012)